Balancing the risks and benefits of parenteral nutrition for preterm infants: can we define the optimal composition?. Issue 1 (12th June 2014) - Embleton, Nicholas D; Morgan, Colin; King, Caroline
Abstract : Nutrient intakes in preterm infants are frequently inadequate and are associated with worse neuro-developmental outcome. Preterm infants take time to establish enteral intakes, and parenteral nutrition (PN) is now an integral component of care. Despite this, the evidence base for PN intakes is extremely limited. There remains uncertainty over safe initial and maximum amounts of macronutrients, and the optimal amino acid and lipid composition. Studies have tended to focus on short-term growth measures and there are few studies with long-term follow-up. There may be a tradeoff between improving cognitive outcomes while minimising metabolic harm that means determining the optimal regimen will require long-term follow-up. Given the importance of appropriate nutrition for long-term metabolic and cognitive health, and the associated healthcare costs, optimising the composition of PN deserves to be seen as a research priority in neonatal medicine.